Domestication provides the key to conservation of Santalum yasi – a threatened Pacific sandalwood. Issue 4 (1st October 2020) - Bush, D.; Thomson, L.; Bolatolu, W.; Dutt, S.; Hamani, S.; Likiafu, H.; Mateboto, J.; Tauraga, J.; Young, E.
ABSTRACT: Santalum yasi is a high-value hemiparasitic tree endemic to Fiji, Niue and Tonga. It has been overexploited for its oil-yielding heartwood and is now threatened. Remaining stands lack genetic diversity and are likely to be suffering from inbreeding depression, although the species still has significant genetic diversity overall. We argue that the best way to conserve this species is through an active domestication program that will adequately sample and conserve the genetic base in ex situ and circa situm plantings. The approach to S. yasi tree-breeding can be characterised as a low-input strategy involving the early use of molecular markers for population parameter determination. Long-term success will have strong interdependent links with the conservation of the remaining genetic resources. A strategy based on recurrent selection and breeding for key traits—including heartwood volume and oil yield per year, oil quality and environmental adaptability related to cyclone resistance and the tolerance of pests and diseases—is recommended. The establishment of genetic conservation stands based on collections of the species throughout its natural range in Fiji and Tonga has commenced. Challenges associated with the conservation and domestication of S. yasi are discussed. These include the advanced age required before oil characterisation can be undertaken; the need to assess genotype–host-plant interactions; and the need for comparatively sophisticated equipment and destructive harvesting to carry out oil assessments. Capacity development of professional staff in the Pacific Islands is an additional prerequisite for implementing an effective strategy. Research into the variation and heritability of heartwood formation and oil characteristics, and a better understanding of the breeding biology of S. yasi and geneflow between it and exotic Indian sandalwood ( S. album ), are high priorities. It will be more than a decade—probably around 20 years—before S. yasi individuals in planned, well-designed trial plantings have sufficient heartwood development to enable oil-trait assessment. Establishment of such trials is an immediate priority. In addition to this long-term activity, we recommend a simple interim strategy that promotes high genetic diversity of seedling-based planting stock. This can be implemented using a combination of gene conservation stands, progeny trials that can be culled to seedling seed orchards, and genetically diverse community-based seed stands. The strategy will both provide a safeguard against the further loss of diversity and promote wide outcrossing. Releasing fragmented populations from inbreeding depression is expected to increase general vigour.